Verificação estrutural de uma torre de suspensão treliçada conforme os critérios da norma IEC 60826 - Victor Roberto Verga Mendes (2020)
Bearing in mind the accidents involving overhead transmission line towers in the last years, the revision of the Brazilian codes design procedures applied to these structures arises. The Brazilian code (ABNT NBR 5422:1985) applied to design of transmission lines is outdated, which can lead to risks in the security level of transmission lines systems. The ABNT NBR 5422:1985 does not cover any application of reliability concepts, although it has been widely used in other ABNT publications. Nowadays, a consolidated reference for the elaboration of national standards applied to transmission lines using structural reliability concepts is the IEC 60826, while another traditional standard oriented to steel angle design of transmission lines is the ASCE 10-15. In order to base future Brazilian standards this work proposes design criteria of transmission lines located in Brazil, based on IEC 60826. Structures of transmission lines are more susceptible to wind forces, once it is slender structures with low self-weigh. Therefore, a solid evaluation and up-to-date local wind data velocities leads to a more reliable and realistic structural design. The structural safety of a suspension tower belonging to a transmission line located in the state of Minas Gerais, designed in the ’80s was evaluated with proposed criteria. The safety evaluation was performed based on the structural model developed on ANSYS v.19.2 considering the tower structure isolated, and the utilization factors were determined for each load combination. For wind forces calculation, data of average maximum annual velocities at meteorological stations near the tower location were collected. Afterward, the extreme value theory was applied and the Gumbel distribution was adopted. For the combination of the actions evaluated, the suspension tower structure showed bars with inappropriate security levels, suggesting the need for greater attention to assets of the power utilities.